2013
DOI: 10.1002/mds.25641
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical brain atrophy in Parkinson's disease with visual hallucination

Abstract: VH in PD can occur due to distinctive neuroanatomical involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 38 publications
2
64
0
Order By: Relevance
“…Most of the earlier imaging studies that attempted to explore psychosis in patients with PD focused on the study of visual hallucination [78,[107][108][109][110][111][112][113] (See table 4). Previous reports suggest that VH in PD patients can be correlated either with cortical or subcortical atrophy [113].…”
Section: Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the earlier imaging studies that attempted to explore psychosis in patients with PD focused on the study of visual hallucination [78,[107][108][109][110][111][112][113] (See table 4). Previous reports suggest that VH in PD patients can be correlated either with cortical or subcortical atrophy [113].…”
Section: Psychosismentioning
confidence: 99%
“…Specifically, VH was associated with dysfunction of frontal lobe [78,109,[111][112][113], temporal lobe [78,110], cingulate cortex [112,113], hippocampus [112], parahippocampal, primary and secondary visual cortex [113], thalamus [78], precuneus and cerebellum [111]. A VBM study investigated grey and white matter alterations in PD patients with VH (Patients had mild to moderate disease stages, average disease duration was 10 years, average age at PD onset 53.6 and they were treated with Levodopa) [113]. This study reported grey matter reduction in the prefrontal cortex, cingulate cortex and visual association areas in PD patients with VH.…”
Section: Psychosismentioning
confidence: 99%
“…The PubMed search revealed seven studies that fulfilled our selection criteria [18,19,20,21,22,32,33]. No DTI-based study met the criteria, and only one VBM study analyzed subcortical structures [18].…”
Section: Resultsmentioning
confidence: 99%
“…No DTI-based study met the criteria, and only one VBM study analyzed subcortical structures [18]. Most studies controlled for or excluded subjects with dementia or cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation